The passage grave at Mysinge, Öland, SE Sweden in a long-term perspective - Papmehl-Dufay, Ludvig (Archaeologia Lituana, 2011)
During the latest part of the early Neolithic period around 3500–3300 BC, megalithic tombs in the form of dolmens and passage graves are built in many different parts of Scandinavia. In Denmark thousands of dolmens and hundreds of passage graves are known, and in northern Germany huge number of tombs are documented as well (Midgley, 1992:418ff). On a Swedish level, dense concentrations of tombs are found along the coasts in Scania and western Sweden, as well as in the area Falbygden in central Västergötland (Srömberg, 1971; Persson & Sjögren, 2001; Sjögren, 2004) (see Fig. 1). Outside these core areas, dolmens and passage graves occur sporadically (e.g. Janzon, 2009; Wallin, 2010) and in large parts of the distribution area of the TRB culture, megalithic tombs have not been built. On the island of Öland, one dolmen and three passage graves are located in the parish of Resmo (Arne, 1909; Papmehl-Dufay, 2006; see below). Only one of these has been excavated, namely the southernmost passage grave at Mysinge, which is the focus of the present paper. [...]